Modal Sosial Suku Arfak dalam Usahatani Padi Ladang di Kampung Guentuy Kabupaten Manokwari Papua Barat - Yolanda Holle; Siti Halimatus Sadiyah (Jurnal Ilmiah Membangun Desa dan Pertanian, 2022)
Exploring the potential of social capital as a social strength of society in developing farming becomes the central point of sustainable agricultural development. The Arfak tribe, a farming community, living in the Papua region, has only been introduced to the introduction of upland rice in their farming activities for approximately three years. The study to find the social capital strength of the Arfak Tribe in upland rice farming, the application of upland rice farming, and the relationship between social capital and the application of upland rice farming is the aim of this research. The research was conducted in Guentuy Village, a center for upland rice production from indigenous Papuan farmers. The number of respondents was 84 Arfak Tribe farmers who cultivate field rice. The survey method uses in-depth interviews and field observations of 84 farmers from the Arfak Tribe. Data were analyzed using descriptive statistical analysis and inferential statistics. The results showed that the social capital owned by the Arfak Tribe in upland rice farming included trust in family members, transmigration farmers, and village officials to cooperate, share experiences, work without pay, and provide village funds for upland rice farming. Social interaction between family members, transmigration farmers, and village officials in discussing field rice problems, borrowing equipment from each other, and collaborating is the social capital of the Arfak Tribe’s built-in social networks. The social capital of the Arfak Tribe is in the form of obedience to find sources of consumption, not forbidding farmers to consume rice. Therefore, it gives the Arfak Tribe an opportunity to learn upland rice farming. The study results concluded that the Arfak Tribe had not fully implemented the farming component. The test results show that the social network between members of farmer groups and village officials influences the Arfak Tribe’s belief in implementing field rice farming. Furthermore, the social norms of the Arfak Tribe, which do not prohibit farmers from consuming rice, provide opportunities for Arfak Tribe farmers to learn the seed preparation stage as the initial stage of implementing upland rice farming.